EXPERIMENTING PARTICIPATIVE E-LEARNING IN NON-FORMAL ADULT EDUCATION: THE ESCALADE PROJECT - Siguencia, Luis Ochoa; Marzano, Gilberto; Ochoa-Daderska, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This paper presents the research approach designed for  EScAlADE, an EU funded project that sees the participation of five European countries and focuses on adult participative e-learning. EScAlADE aims at investigating about the educational needs of adults (range: 50-65 years) involved in e-learning programs. This paper reports on the projects methodology and on the necessity of educational strategies able to provide adult trainees with the skills required by the labor market.